ON n-PRIME IDEALS - (:unkn) unknown (UNIV POLITEHNICA BUCHAREST, SCI BULL, 2018)
In this article, we introduce an intermediate classes of ideals between prime and quasi primary ideals, denoted by n-prime, and we focus on some properties of n-prime ideals. Moreover, we defined a topology on the set of all n-prime ideals such that we examine the topological concepts, irreducibility, connectedness, and seperation axioms.
Keywords: prime ideals; prime spectrum; n-prime Ideals; n-prime spectrum; 2-ABSORBING IDEALS; COMMUTATIVE RINGS